Activation of eggshell powder (ESP) using palm oil fuel ash (POFA) and its application in removing lead and cadmium from river water - Badariah, Badariah; Heraningsih, Sarah Fiebrina; Yulistian, Saldi; Rainiyati, Rainiyati; Purwati, Indah; Jailani, M Syahran (Journal of Degraded and Mining Lands Management, 2025)
Contamination by heavy metals, especially lead (Pb) and cadmium (Cd), presents considerable environmental and public health hazards. This study examined the efficacy of a composite adsorbent composed of eggshell powder (ESP) and Palm Oil Fuel Ash (POFA) in eliminating Pb and Cd from polluted river water. BET analysis indicated that the ESP-POFA composite demonstrated enhanced surface area and pore volume post-activation, achieving a peak surface area of 38.79 m²/g at a 1:0.75 ESP:POFA ratio. The peak adsorption efficiency for Pb was 87.16%, achieved at a 1:0.25 ESP: POFA ratio after 180 minutes of agitation, whereas Cd adsorption peaked at 94.17% at a 1:0.75 ratio with the same agitation time. The adsorption capacity fluctuated according to the ESP: POFA ratio, with Pb attaining 0.00038 mg/g at the 1:0.25 ratio and Cd achieving 0.00099 mg/g at the 1:0.75 ratio. The findings demonstrate that the ESP-POFA composite is a sustainable and economical solution for water treatment and is exceptionally proficient in removing cadmium from river water. These findings endorse the composite's potential for extensive water treatment applications; nevertheless, additional modification is necessary to enhance Pb adsorption capability.